2010
DOI: 10.1088/0264-9381/27/22/225023
|View full text |Cite
|
Sign up to set email alerts
|

The Carter constant for inclined orbits about a massive Kerr black hole: I. Circular orbits

Abstract: In an extreme binary black hole system, an orbit will increase its angle of inclination (ι) as it evolves in Kerr spacetime. We focus our attention on the behaviour of the Carter constant (Q) for near-polar orbits; and develop an analysis that is independent of and complements radiation reaction models. For a Schwarzschild black hole, the polar orbits represent the abutment between the prograde and retrograde orbits at which Q is at its maximum value for given values of latus rectum (l) and eccentricity (e). T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(24 citation statements)
references
References 43 publications
(146 reference statements)
2
22
0
Order By: Relevance
“…In Section 2 we shall analytically derive the formula for ι for elliptical orbits on the abutment, and thus confirm the result for ∂ι/∂˜ min [42], which was derived numerically for circular orbits. In addition, we shall analytically derive ∂ι/∂ for elliptical orbits that evolve on the abutment.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…In Section 2 we shall analytically derive the formula for ι for elliptical orbits on the abutment, and thus confirm the result for ∂ι/∂˜ min [42], which was derived numerically for circular orbits. In addition, we shall analytically derive ∂ι/∂ for elliptical orbits that evolve on the abutment.…”
Section: Introductionsupporting
confidence: 71%
“…It was found that X ± = − X 2 ± in the vicinity of the abutment (see Section 3.5 in Komorowski et al [42]); therefore,…”
Section: Orbital Angle Of Inclination ιmentioning
confidence: 97%
See 3 more Smart Citations